The effects of the interaction between the type of Visual Cue and its display style via digital mobile content on the development of immediate and delayed cognitive achievement among middle school students in the English language curriculum - Awwaf, Taher Ali; Zaidan, Ashraf Ahmed (Journal of Educational and Psychological Sciences, 2020)
This study investigated the effect of the interaction between the type of visual cue (Color vs. Bordering cue) and its display style (Fixed vs. Flexible display) via digital mobile content on the development of immediate and delayed cognitive achievement among middle school students in the English Language curriculum, The study tool used achievement test and the sample consisted of 60 first intermediate school students in Jazan, divided into four experimental treatments according to the experimental design of the research. After designing an appropriate digital mobile content program; Immediate and delayed achievement test was applied. Two-Way ANOVA are used. The results indicated as follows; • There were no statistically significant differences between experimental groups exposed to the type of visual cue (Color vs. Bordering) on the immediate and delayed cognitive achievement regardless of the visual cues’ display style used. • There were statistically significant differences in related to the effect of visual cues’ display style (Fixed vs. Flexible) in favor of the experimental groups, which was exposed to a flexible display style on the immediate and delayed cognitive achievement regardless of the type of visual cue used. • The results also indicated no significant impact of the interaction between to the type of visual cue and its display style on the immediate and delayed cognitive achievement.